Serrated polyps of the colon and rectum: Remove or not? - Sano, Wataru (World J Gastroenterol, 2020)
In recent years, the serrated neoplasia pathway where serrated polyps arise as a colorectal cancer has gained considerable attention as a new carcinogenic pathway. Colorectal serrated polyps are histopathologically classified into hyperplastic polyps (HPs), sessile serrated lesions, and traditional serrated adenomas; in the serrated neoplasia pathway, the latter two are considered to be premalignant. In western countries, all colorectal polyps, including serrated polyps, apart from diminutive rectosigmoid HPs are removed. However, in Asian countries, the treatment strategy for colorectal serrated polyps has remained unestablished. Therefore, in this review, we described the clinicopathological features of colorectal serrated polyps and proposed to remove HPs and sessile serrated lesions ≥ 6 mm in size, and traditional serrated adenomas of any size.